A capital dos esportes: poder, idealismo e hábitos físico-esportivos no surgimento de Goiânia (1930-1945) - Jean Carlo Ribeiro (2020)
This research aims to describe and analyze the sporting context of the city of Goiânia, associated with the political advent of its projection, foundation and consolidation among the years of 1930 and 1945. For a deeper understanding and contextualization of the approached theme, literary works on development of sport in Brazil were consulted until the first half of the 20th and in Goiás until the mid-1930s. Were also included in this collection, publications on the Goiania historiography relevant to the historical outline proposed for the research, works of both academic and memorialist character. As a complementary source of research, official public documents were investigated, such as laws, decrees, minutes, reports, regulations, statutes, censuses and constitutions of the state of Goiás. The Situationist written press was used as the main source of this research, materialized in the publications of the newspapers “Correio Oficial - Estado de Goiaz” (between 1930 and 1943) and “O Popular” (between 1938 and 1945). Through these, local public authorities would endeavor to impose a new social order. The arising of Goiânia as the new capital of the state of Goiás would be highlighted as a significant transformation for the region, which still in 1930 would have its image linked to isolation and backwardness. Included in this purpose, sports practices would be part of the set of this political program that intended to cultivate new habits, customs and experiences that would feed a modernized urban culture, although the models of structuring, institutionalization, management, organization and practice of sports, continued from 1935, to a large extent, with similar characteristics and formed by the same groups and mobilizing agents who managed these before the new capital exists.